The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1177/0093650211408594
|View full text |Cite
|
Sign up to set email alerts
|

Identification as a Mechanism of Narrative Persuasion

Abstract: To provide a causal test of identification as a mechanism of narrative persuasion, this study uses the perspective from which a story is told to manipulate identification experimentally and test effects on attitudes. In experiment 1, 120 participants read a story that was told either from the perspective of one character or another character, with both characters having opposing goals. Results showed that perspective influenced identification and story consistency of attitudes. Moreover, identification with on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
230
1
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(277 citation statements)
references
References 29 publications
(72 reference statements)
11
230
1
14
Order By: Relevance
“…In recent years researchers have become particularly interested in the mechanisms and boundary conditions that are responsible for the persuasiveness of stories and the increased attitude change that seems to be caused by deeper transportation into the story world. One family of explanations revolves around emotional processes and the empathy or identification with a character (e.g., De Graaf, Hoeken, Sanders, & Beentjes, 2012; Hoeken & Sinkeldam, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In recent years researchers have become particularly interested in the mechanisms and boundary conditions that are responsible for the persuasiveness of stories and the increased attitude change that seems to be caused by deeper transportation into the story world. One family of explanations revolves around emotional processes and the empathy or identification with a character (e.g., De Graaf, Hoeken, Sanders, & Beentjes, 2012; Hoeken & Sinkeldam, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In the field of narrative persuasion, it has been shown that identification with characters plays an important mediating role: For a narrative to cause a persuasive impact there must be a high identification with the characters involved (de Graaf et al, 2012;Hoeken & Fikkers, 2014;Igartua & Barrios, 2012;Igartua & Vega, 2016). In this context, identification with characters is a cognitive-affective process that takes place during reception (reading, viewing) of the narrative message, and that is linked to perspective-taking or cognitive empathy (putting oneself in the shoes of the character), emotional empathy (feeling the same emotions as the character), and the temporary loss of self-awareness (the receiver of the narrative imagines being the character, taking on his or her identity, and becoming merged with the character) (Cohen, 2001;Igartua & Barrios, 2012;Moyer-Gusé, 2008).…”
Section: Similarity Identification With Characters and Persuasive Imentioning
confidence: 99%
“…A narrative always provides information (and implicit or explicit arguments) based on which individuals can change or adapt their beliefs, attitudes and behaviors. Research into narrative persuasion studies the processes or mechanisms that explain how narratives can change attitudes, beliefs or behaviors (de Graaf, Hoeken, Sanders, & Beentjes, 2012;Green & Brock, 2000;Hoeken & Fikkers, 2014;Igartua & Barrios, 2012). A meta-analysis review has shown that narratives have significant effects on attitudes, beliefs, behavioral intention and behavior (Braddock & Dillard, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Estimular la imaginación del receptor es activar la atención, pues significa implicar cognitivamente al receptor en el mensaje a través de procesos vicarios de identificación y proyección (De Graaf, Hoeken, Sanders y Beentjes, 2012;Rodero, Alonso González y Fuentes Abad, 2004). Para ello, el engagement con la narración debe basarse en un rápido planteamiento del estado inicial de la historia (De Graaf, Hoeken, Sanders y Beentjes, 2009;Busselle y Bilandzic, 2009).…”
Section: Introductionunclassified